International Myeloma Working Group immunotherapy committee consensus guidelines and recommendations for optimal use of T-cell-engaging bispecific antibodies in multiple myeloma - Rodriguez-Otero, Paula; Usmani, Saad; Cohen, Adam D; van de Donk, Niels W C J; Leleu, Xavier; Gállego Pérez-Larraya, Jaime; Manier, Salomon; Nooka, Ajay K; Mateos, Maria Victoria; Einsele, Hermann; Minnema, Monique; Cavo, Michele; et al. (The lancet. Oncology, 2024)
Multiple myeloma remains an incurable disease, despite the development of numerous drug classes and combinations that have contributed to improved overall survival. Immunotherapies directed against cancer cell-surface antigens, such as chimeric antigen receptor (CAR) T-cell therapy and T-cell-redirecting bispecific antibodies, have recently received regulatory approvals and shown unprecedented efficacy. However, these immunotherapies have unique mechanisms of action and toxicities that are different to previous treatments for myeloma, so experiences from clinical trials and early access programmes are essential for providing specific recommendations for management of patients, especially as these agents become available across many parts of the world. Here, we provide expert consensus clinical practice guidelines for the use of bispecific antibodies for the treatment of myeloma. The International Myeloma Working Group is also involved in the collection of prospective real-time data of patients treated with such immunotherapies, with the aim of learning continuously and adapting clinical practices to optimise the management of patients receiving immunotherapies.